Albania : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
The Selected Issues paper analyzes the determinants of growth in Albania, the macroeconomic underpinnings for growth, the role of remittances in the economy, and the policy response to rapid credit growth. It also analyzes the official estimates with estimates from various macroeconomic surveys, and discusses the implications for the structure of the balance of payments. It also provides a framework for analyzing the budgetary impact of remittances in Albania, and examines the acceleration of credit growth and the policy options available to address the resulting macroeconomic and prudential concerns.